1994
DOI: 10.1136/oem.51.4.244
|View full text |Cite
|
Sign up to set email alerts
|

Pleural mesothelioma and exposure to asbestos: evaluation from work histories and analysis of asbestos bodies in bronchoalveolar lavage fluid or lung tissue in 131 patients.

Abstract: Exposure to asbestos was evaluated in 131 patients with pleural malignant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Median values were 121 AB·mL -1 in asbestosis, 5 AB·mL -1 in benign pleural disease and 4 AB·mL -1 in exposed workers without evidence of an asbestos-related disease. Similar results have been published in smaller series of patients [39,43,44].…”
Section: Bronchoalveolar Lavagesupporting
confidence: 79%
“…Median values were 121 AB·mL -1 in asbestosis, 5 AB·mL -1 in benign pleural disease and 4 AB·mL -1 in exposed workers without evidence of an asbestos-related disease. Similar results have been published in smaller series of patients [39,43,44].…”
Section: Bronchoalveolar Lavagesupporting
confidence: 79%
“…Most studies concerned with asbestos fibres or bodies in the human lungs have compared their concentrations with exposure characteristics and/or associated diseases in specific groups [10][11][12][13][14][15]. The changes in the use of asbestos have only been taken into account exceptionally in the interpretation of mineralogical findings [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that malignant mesothelioma is a neoplasm associated with asbestos exposure [Carbone et al, 2002]; however, no definite evidence of exposure to asbestos could be found in the work histories of some patients [Pairon et al, 1994;Hirvonen et al, 1999]. These investigations suggest that there are other factors involved in the pathogenesis of malignant mesothelioma.…”
Section: Introductionmentioning
confidence: 92%